Effect of the critical shoulder angle on severe cranialization following total shoulder arthroplasty - Wolf, Matthias (J Orthop, 2020)
PURPOSE: This study assesses the relationship of CSA, cranialization and radiographic glenoid loosening following TSA in the long-term follow-up. METHODS: 26 shoulders with TSA were examined radiographically postoperatively and after a mean 12.6 years. Severe cranialization was defined as direct humeral contact with the acromion and/or acetabularization of the acromion. RESULTS: A CSA ≥35° was associated with severe cranialization. Glenoid loosening was present in 6/24 shoulders (25%). Severe cranialization was associated with glenoid loosening (p = 0.003). CONCLUSION: A postoperative CSA ≥ 35° was associated with severe humeral cranialization after TSA in the long-term follow-up. Severe cranialization correlated with glenoid loosening. Level of evidence IV – retrospective cohort study.